ESTIMASI DAYA TAMPUNG BEBAN PENCEMARAN ORGANIK DI DAERAH ALIRAN SUNGAI LEMBU KECAMATAN SINGINGI - Zarrin Mastur; Thamrin ' Thamrin; Bintal Amin (Program Pascasarjana Universitas Riau, 2014)
Research conductedin September 2011 to April 2012. The purpose is to asses thenumber of land-based activities that give rise to organic waste along SungaiLembu, in terms of BOD and dissolved oxygen content. The estimate of the organicpollution load capacity of each point of observation activities. The method used waspurposive sampling method with the consideration that the location of an area or apotential pollutant souces contributing to the pollution load of Sungai Lembu.Results showed that the organic substance content of BOD measurements at severallocations showed still under water quality standaed II class PP. 82 in 2001 and isbased on the calculation of organic pollution load capacity at each observationlocation is higher than the pollution load.